Android-based Video Sharing Application Design - Anastasia Siwi Fatma Utami; Muhammad Saifudin Arif; Ahmad Sinnun; Feri Prasetyo; Nicodias Palasara (Jurusan Informatika Universitas Tanjungpura, 2023)
The impact of the COVID-19 virus pandemic that has hit the whole world has more or less affected the way people move. Many activities have to be centered at home, from working at home to studying at home. On the other hand, students at school still need tutoring. However, the signs of returning to school amid the rules of Large-Scale Social Restrictions (PSBB) and Adaptation of New Habits (IMR) still appear gray. The final solution is to keep children learning online. Online learning is learning that is done online, using learning applications and social networks. Online learning is learning that is done without face-to-face, but through an available platform. For example in this mobile application which aims to assist the learning process for students and teachers. This learning video application is made for learning and teaching tools. The process of designing this educational video sharing information system begins with analyzing the learning system, designing UML diagrams, and designing mock ups as an interface for an overview of the application. The result of this final project is as an encouragement for students who are expected to be better by using a system that has not been computerized